Treatment of rotablation‐induced ostial left circumflex perforation by papyrus covered stent and its fenestration to recover the left anterior descending artery during CHIP procedure. Issue 6 (21st February 2019) - Adusumalli, Srikanth; Gaikwad, Niranjan; Raffel, Chris; Dautov, Rustem
Abstract: Coronary artery perforation is a rare complication of percutaneous coronary intervention (PCI). Covered stents have been successfully used in these situations. We report a case of ostial left circumflex (LCx) artery perforation during rotablation PCI of left main coronary artery (LMCA) and LCx artery. After failed attempts to balloon tamponade the perforation, a PK Papyrus covered stent was deployed from proximal LCx into LMCA. This resulted in acute exclusion of the left anterior descending (LAD) artery from coronary circulation. Using a dual lumen catheter, a stiff wire was advanced through the side port toward the occluded LAD to fenestrate the membrane of the covered stent. A series of balloons were used to dilate the fenestration in the covered stent to restore a normal flow into the LAD.